The legal obstacles to the universality of human rights - Djagham, mohamed; Benmecheri, Abdelhalim (Revue jurisprudence, 2019)
The universality of human rights is subject to a number of legal obstacles, the most important of which is the possibility of States to dispose of their international obligations. They have the freedom to ratify and the possibility of reservation, to disable and restrict rights and even to withdraw from international conventions on human rights. the possibilty to opt out from international human rights obligations is in a paradoxale relationship with universality ,because it is a motivation for the state to join on the one hand, and on the other, they can void human rights conventions of their content and create gaps in the global commitment network.